Development Of an Electronic Module for Antidiabetic Testing Techniques as A Guide for Pharmacy Students in Pharmacology Practicum and Research - Ihwan; Yuliet; Moh. Tahir; Ahmad Ramadhan (Postgraduate, University of Mataram, 2025)
The era of the 4.0 revolution is a time characterized by the development of information technology. This era offers opportunities for digitalization in various fields, including higher education. One area that greatly requires information technology is research, particularly in the development of electronic modules as learning media. This study aims to develop an electronic module on antidiabetic testing techniques as a guide for practice and research. The research method used is a Research and Development design, utilizing the ADDIE approach model (Analysis, Design, Development, Implementation, and Evaluation). The module used was validated by two content and language experts, two media expert validators, and validated for feasibility by 128 respondents using a questionnaire instrument, and the effectiveness evaluation of the module was tested by 36 students from the Pharmacy Department of Tadulako University. The research results show that the validity test by two content experts rated it as feasible with an average score of 4 and a percentage of 80%, the language expert rated it as very feasible with a percentage of 88.0% and an average score of 4.4, the design expert rated it as very feasible with a percentage of 92.22% and an average score of 4.6, the feasibility assessment by students rated it as very feasible to be used as learning media with an average score of 4.05 and a percentage of 81.02%, and the effectiveness test using N-Gain was 89%. This electronic module establishes a framework for developing interactive instructional materials in scientific education, particularly relevant to pharmaceutical sciences and healthcare fields, through its systematic integration of practical simulations and pharmacological research components within the learning environment.